Karyological study on 12 Centaurea (Asteraceae) species from Turkey - Aksoy, Huseyin; Berber, Ahmet A.; Celik, Sezgin; Baser, Birol; Karaveliogullari, Faik A. (FIRENZE UNIV PRESS, 2016)
The purpose of this study was to determine chromosome morphology and karyological features of 12 Centaurea L. species belonging to sections Cynaroides Boiss. ex Walp. and Phaeopappus (DC.) Boiss. from Anatolia, Turkey. The chromosome numbers were determined as 2n = 18 in all species. Karyotype analyses were made in detail for the first time for all species except Centaurea kurdica Reichardt, Centaurea fenzlii Reichardt and Centaurea amanicola Hub.-Mor. Chromosome counts of three of them (Centaurea foliosa Boiss. et Kotschy ex Boiss., Centaurea haussknechtii Boiss., Centaurea gigantea Sch. Bip. ex. Boiss.) were given for the first time. The classification of chromosomes and the lengths of long and short arm, haploid chromosome lengths, arm ratios, relative sizes and centromeric positions were represented for all species. Also, photographs of metaphase chromosomes and ideograms are given for studied Centaurea taxa. A distribution map of studied taxa is provided.
Keywords: Turkey; Centaurea; chromosome; karyotype; CHROMOSOME COUNTS; SECT. ACROCENTRON; CARDUEAE; Plant Sciences; Genetics & Heredity